2013
DOI: 10.9755/ejfa.v25i8.16092
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality and safety of dietary supplements sold in Saudi<br>Arabia

Abstract: The global market for dietary supplements has advanced in recent years capitalizing on the growing awareness of healthy living worldwide. Supplements provide enhanced nutritional levels for daily competitive performance. However, there is a need to explore the quality of dietary supplements as there are few studies related to this area. Therefore, the objective of this study was to determine the microbiological quality of dietary supplements in the local markets of Saudi Arabia. The total bacterial count, coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…A majority of the athletes reported that supplements are safe and can be consumed without any harm [22,23]. Our results showed that a majority of athletes (n = 75; 45.73%) also agreed that energy drinks are safe to consume, which is similar to a previous study [24], in which the main reason given for using energy drinks was to gain energy in general and to help compensate for a lack of proper sleep (12.8%).…”
Section: Discussionsupporting
confidence: 87%
“…A majority of the athletes reported that supplements are safe and can be consumed without any harm [22,23]. Our results showed that a majority of athletes (n = 75; 45.73%) also agreed that energy drinks are safe to consume, which is similar to a previous study [24], in which the main reason given for using energy drinks was to gain energy in general and to help compensate for a lack of proper sleep (12.8%).…”
Section: Discussionsupporting
confidence: 87%
“…In earlier studies [12], it was noted that the use of energy drinks among college students was primarily to enhance performance. Similarly, in a study involving Saudi students, 73% of the students reported using energy drinks to enhance performance objectives [11].…”
Section: Discussionmentioning
confidence: 96%
“…For college athletes, consuming even small doses of caffeine (1 -2 mg/kg body mass) can influence reaction time, alertness, and visual information processing, which are crucial during exercise, practice, and competition. However, overdosing can negatively affect reaction time and alertness [11]. Therefore, the objective of this study was to access the usage patterns of energy drinks among college Students in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this, even imported products such as energy drinks have been shown to be a potential risk factor for the development of microbial hazards. In addition, there is very limited published information regarding the quality and safety of these products in Saudi Arabian markets [11]. Therefore, in this study we tested the microbiological quality of these drinks to ensure that the products are safe.…”
Section: Saudi Arabiamentioning
confidence: 99%
“…The samples were collected based on the protocol described earlier by Aljaloud et al [11]. The numbers of samples were based on the availability of drinks in a particular district of Riyadh.…”
Section: Samplingsmentioning
confidence: 99%